2001
DOI: 10.1289/ehp.011091127
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous abortion, sex ratio, and paternal occupational exposure to 2,3,7,8-tetrachlorodibenzo-p-dioxin.

Abstract: There is conflicting research regarding an association between fetal death and paternal exposure to Agent Orange, a phenoxy herbicide widely used in Vietnam that was contaminated with 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD). Men who worked in the U.S. factories that produced Agent Orange were exposed to TCDD at levels hundreds of times higher than TCDD levels in the general population. Wives of TCDD-exposed chemical workers and wives of nonexposed neighborhood referents were interviewed to determine reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
1
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 28 publications
2
23
1
2
Order By: Relevance
“…in the Seveso incident (Mocarelli et al 1996(Mocarelli et al , 2000 and differ from what has been reported for the U.S. chlorophenol cohort (Schnorr et al 2001). …”
Section: Boys Girlscontrasting
confidence: 77%
See 1 more Smart Citation
“…in the Seveso incident (Mocarelli et al 1996(Mocarelli et al , 2000 and differ from what has been reported for the U.S. chlorophenol cohort (Schnorr et al 2001). …”
Section: Boys Girlscontrasting
confidence: 77%
“…Moshammer and Neuberger (2000) reported a small difference of 0.46 in an Austrian worker cohort; Rogan et al (1999) found a slightly higher value of 0.49 in the Yu-cheng rice oil victims; and Michalek et al (1998) found no effect for this outcome in the lowly exposed Ranch Hand cohort by American Vietnam veterans who sprayed Agent Orange. In a conflicting study, no effect on the sex ratio was detected in a recent publication (Schnorr et al 2001) from producers of pesticides in two U.S. cohorts that had high TCDD exposure.…”
mentioning
confidence: 93%
“…O comprimento ao nascer está intimamente relacionado com o peso do neonato, entretanto a interrupção do desenvolvimento intrauterino pode caracterizar-se como a ocorrência de um abortamento espontâneo. Este consiste em uma das complicações mais comuns durante a gravidez, podendo apresentar uma incidência entre 6,5% e 21% em gestações clinicamente reconhecidas, ocorrendo na maioria dos casos entre a 7 a e a 15 a semana de gestação 26,34 . A etiologia do abortamento espontâneo é heterogênea e inclui fatores genéticos e ambientais.…”
Section: Resultsunclassified
“…In addition to these effects, a decreased male/female sex ratio among children born to males who were exposed to TCDD at a relatively young age compared with unexposed males has also been reported [15,16,20]. On the other hand, it was reported in a human cohort study that no association was found between paternal serum TCDD levels and the sex ratio of offspring [21]. These conflicting reports suggest that further investi- Sex ratio of the offspring in the control and T2000/400 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Ryan et al [20], in a study conducted in Ufa, Russia, suggest that human exposure to high levels of dioxin is associated with the birth of more girls only in cases of paternal exposure. In contrast, the sex ratio among offspring is not markedly affected among humans exposed to a phenoxy herbicide containing TCDD and produced in the US factories which manufactured Agent Orange [21], and Yoshimura et al [25] found that the sex ratio was not significantly different from normal (0.513) in Yusho victims after accidental massive exposure to polychlorinated biphenyls (PCBs) and polychlorinated dibenzofurans (PCDFs). Despite these epidemiological studies, few studies have examined the possibility that the exposure of laboratory animals to TCDD, and especially the exposure of males, could lead to a lower male/ female sex ratio.…”
mentioning
confidence: 99%